PENGARUH BEBAN KERJA TERHADAP KINERJA KARYAWAN DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING PADA APOTEK KELUARGA AREA KOTA PEKANBARU - Gultom, Elida; Syafrina, Nova (Jurnal Daya Saing, 2025)
This research aims to determine the effect of workload on employee performance with work stress as an intervening variable. The population in this study was all operational employees in the Pekanbaru City Family Pharmacy area, namely 150 people. The sampling technique uses a census sample, so that the entire population is sampled. The data analysis technique uses Path Analysis with the help of the SPSS Version 25 Program and the Sobel Test. The research results show that workload and work stress directly have a negative and significant effect on employee performance. Workload has a positive and significant effect on work stress. Workload also has a negative effect on employee performance through work stress.